MBCL-25. PILOT STUDY OF A SURGERY AND CHEMOTHERAPY-ONLY APPROACH IN THE UPFRONT THERAPY OF CHILDREN WITH WNT-POSITIVE STANDARD RISK MEDULLOBLASTOMA: UPDATED OUTCOMES. (4th December 2020) - Cohen, Kenneth; Chi, Susan; Hawkins, Cynthia; Rodriguez, Fausto; London, Wendy; Castellino, Robert Craig; Aguilera, Dolly; Stapleton, Stacie; Ashley, David; Landi, Daniel; Bandopadhayay, Pratiti
Abstract: BACKGROUND: Wnt+ medulloblastoma (WPM) is a favorable subtype with EFS > 90% when treating postoperatively with craniospinal irradiation and posterior fossa boost (CSI/XRT) followed by adjuvant chemotherapy. This pilot study explored the safety of omitting radiation in standard-risk WPM. METHODS: Subjects had to meet standard-risk criteria (< 1.5 cm2 residual tumor, no metastatic spread, no anaplasia) and have a WPM. Subjects received chemotherapy following the COGACNS0331 AAB-AAB-AAB (A=cisplatin/CCNU/VCR; B=cyclophosphamide/vincristine) backbone. RESULTS: Six children were enrolled on study treatment prior to early study closure. Subject #1 completed planned protocol therapy but relapsed 3 months following the completion of therapy. Subject #2 completed planned protocol therapy but relapsed 6 months following the completion of therapy. In both cases, relapse was local and disseminated. Further accrual was halted. Both subjects were salvaged with CSI/XRT followed by adjuvant chemotherapy. Of the remaining 4 subjects, two had recently completed planned protocol therapy at the time of study closure and received CSI/XRT while in remission and remain in remission approximately one year from the completion of treatment. One subject aborted protocol therapy and transitioned to a Head Start regimen and remains in remission 10 months from completion of therapy. The final subject had just completed protocol therapy and had new areas of restricted diffusion concerning for early relapse. Went on to receive CSI/XRT but subsequently relapsed and is now receiving salvage chemotherapy. CONCLUSIONS: Chemotherapy following ACNS0331, omitting CSI/XRT, appears to be insufficient for the treatment of non-metastatic WPM.